К познанию сирфид-афидофагов (Diptera, Syrphidae) Украинских Карпат - Аникина, З.Л. (Вестник зоологии, 1971)
As a result of examination of three groups of the Ukrainian, Carpathians landscapes
(piedmont, low-mountain, mid-mountain), 80 species of hover flies-aphydophages of 16
genera from two subfamilies (Syrphinae — 68, Chelosiinae — 12 species) are found. The
trophic relations of larvae of eight hover flies' species are stated.